Evaluation of estrogenic and antiestrogenic activity in sludge and explanation of individual compound contributions - Černá, Tereza; Ezechiáš, Martin; Semerád, Jaroslav; Grasserová, Alena; Cajthaml, Tomáš (Journal of hazardous materials, 2022)
Mixture toxicity, including agonistic and antagonistic effects, is an unrevealed environmental problem. Estrogenic endocrine disruptors are known to cause adverse effects for aquatic biota, but causative chemicals and their contributions to the total activity in sewage sludge remain unknown. Therefore, advanced analytical methods, a yeast bioassay and mixture toxicity models were concurrently applied for the characterization of 8 selected sludges with delectable estrogenic activity (and 3 sludges with no activity as blanks) out of 25 samples from wastewater treatment plants (WWTPs). The first applied full logistic model adequately explained total activity by considering the concentrations of the monitored compounds. The results showed that the activity was primarily caused by natural estrogens in municipal WWTP sludge. Nevertheless, activity in a sample originating from a car-wash facility was dominantly caused by partial agonists - nonylphenols - and only a model enabling prediction of all dose-response curve parameters of the final mixture curve explained these results. Antiestrogenic effects were negligible, and effect-directed analysis identified the causative chemicals.
Keywords: WWTP sludge; Endocrine Disruptors; endokrinní disruptory; estrogeny; antagonisté estrogenu; Estrogen Antagonists; Antagonistic activity; Mixture toxicity; Estrogens; odpadní vody; chemické látky znečišťující vodu; Agonistic activity; Constructed wetland; Water Pollutants, Chemical; Sewage